Characterization of fertilization-modulated myelin basic protein kinases from sea star: Regulation of Mapk - Lefebvre, Diana L.; Charest, David L.; Yee, Arthur; Crawford, Bruce J.; Pelech, Steven L. (Journal of cellular biochemistry, 1999)
The myelin basic protein (MBP)‐phosphorylating enzymes present during maturation and early embryogenesis of the sea star (Pisaster ochraceus) were investigated. The major maturation‐activated MBP kinase (p45 Mapk) was molecularly cloned based on tryptic sequence information obtained with the purified enzyme and shown to be highly related to human Erk1 with 76% amino acid identity. Kinase assays and immunoblotting studies revealed that Mapk remained highly active until 12 h post‐fertilization (PF), after which it declined. By 4 days PF, Mapk protein was no longer detectable. At 3 h PF, about half of the detectable MBP phosphotransferase activity could be attributed to a 75 kDa protein kinase that was distinct from Mapk. Like Mapk, this protein phosphorylated MBP mostly on threonine residues, but it failed to phosphorylate a peptide (APRTPGGRR) based upon the Thr‐97 MAP kinase phosphorylation site in MBP. Rather, it phosphorylated a peptide (AAQKRPSQRTKYLA) patterned after the N‐terminus of MBP. Our studies also showed a dramatic increase in MBP phosphotransferase activity occurred by 4 days PF that arose from a third kinase that phosphorylated MBP solely on serine residues. This kinase exhibited the following substrate substrate preference: AAQKRPSQRTKYLA, peptide substrate for S6 kinases (AKRRRLSSLRASTSKSESSQK) > MBP > histone H1 > prota‐mine > casein > APRTPGGRR. This kinase was not appreciably affected by addition of phosphatidylserine/diacylglycerol, or the staurosporine analogue Roche Compound 3, but it was partly inhibited by a protein kinase C pseudosubstrate peptide. Gel filtration analysis revealed an apparent molecular mass of 41 kDa for the enzyme. Therefore, at least two novel MBP‐phosphorylating enzymes distinct from Mapk are preferentially activated following fertilization and early embryogenesis of the sea star. J. Cell. Biochem. 75:272–287, 1999. © 1999 Wiley‐Liss, Inc.